Comparing implementations of self-interacting dark matter in the gizmo and arepo codes. Issue 2 (18th April 2022) - Meskhidze, Helen; Mercado, Francisco J; Sameie, Omid; Robles, Victor H; Bullock, James S; Kaplinghat, Manoj; Weatherall, James O
ABSTRACT: Self-interacting dark matter (SIDM) models have received great attention over the past decade as solutions to the small-scale puzzles of astrophysics. Though there are different implementations of dark matter (DM) self-interactions in N-body codes of structure formation, there has not been a systematic study to compare the predictions of these different implementations. We investigate the implementation of dark matter self-interactions in two simulation codes:gizmo and arepo . We begin with identical initial conditions for an isolated 10 10  M⊙ dark matter halo and investigate the evolution of the density and velocity dispersion profiles in gizmo and arepo for SIDM cross-section over mass of 1, 5, and 50 $\rm cm^2\, g^{-1}$ . Our tests are restricted to the core expansion phase, where the core density decreases and core radius increases with time. We find better than 30 per cent agreement between the codes for the density profile in this phase of evolution, with the agreement improving at higher resolution. We find that varying code-specific SIDM parameters changes the central halo density by less than 10 per cent outside of the convergence radius. We argue that SIDM core formation is robust across the two different schemes and conclude that these codes can reliably differentiate between cross-sections of 1, 5, and 50 $\rm cm^2\, g^{-1}$, but finer distinctions would require further investigation.